DEVELOPMENT OF ANDROID-BASED AUGMENTED REALITY LEARNING MEDIA FOR THE CONCEPT OF MOLECULAR GEOMETRY - Karismayani, Karismayani; Imanda, Riska; lukman, Isna Rezkia (FKIP USK, 2025)
The integration of Augmented Reality (AR) technology into educational media has the potential to enhance student engagement and understanding of abstract concepts. This study aimed to develop and evaluate the quality of AR-integrated learning media for teaching molecular structures in chemistry. Using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model, this research employed a systematic approach that encompassed five stages of development. The study was conducted with two eleventh-grade classes at a public high school (SMA Negeri 1 Lhokseumawe), involving 66 students as the subjects of the research. Expert validation of the developed media yielded a score of 88, which categorizes it as